Spaces for skateboarding in the city–new spatial concepts beyond skateparks - Kilberth, Veith (Frontiers in Sports and Active Living, 2025)
Since the 1990s, skateboarding has emerged as a significant urban practice, often resulting in spatial conflicts. The predominant response from municipal authorities has been to confine skateboarding to purpose-built skateparks, overlooking more integrated and inclusive spatial solutions. This study critically examines this approach and explores alternative skateboarding spaces within the framework of urban sociological discourse on the creative city phenomenon and the evolving collaboration between skateboarding communities and city authorities. Employing a praxeological approach, the analysis integrates cultural theory, discourse analysis, and fieldwork. Building on existing literature, the study is complemented by case study analyses of skateboarding spaces worldwide. To provide a structured understanding, a spatial typology is developed, encompassing purpose-built skateparks, self-constructed DIY projects, shared spots, and legalized street spots. These spaces are conceptualized along the axes of exclusion vs. inclusion and subcultural vs. sportification. Key opportunities and essential conditions for the implementation of innovative spatial concepts in urban environments are identified, with particular emphasis on the pivotal role of collaboration between skateboarding communities and municipal authorities. By presenting a theoretical framework for diversifying skateboarding spaces, the findings contribute to the urban planning discourse and promote participatory urban development and design.